SIMULATION MODELING OF INTERPLANETARY SHOCKS ARRIVAL TIME PREDICTION ON HISTORICAL DATA SET - Turchenko, Volodymyr; Demchuk, Viktor; Sachenko, Anatoly (International Journal of Computing, 2014)
An approach to prediction of the arrival time of interplanetary shocks using neural networks based on the data gathered from single EPAM (Electron, Proton and Alpha Monitor) channel of NASA’s ACE (Advanced Composition Explorer) spacecraft is proposed in this paper. A short description of ACE spacecraft and the data, published online on the appropriate web-site, are considered. A data choice to fulfill a prediction of interplanetary shocks is proven and structure of neural network is described. The results of simulation modeling in MATLAB are considered in the end of the paper.